Wild Scandinavia [videorecording (DVD)] (PBS, 2023)
Immerse in three iconic Scandinavian landscapes: the hauntingly beautiful coast; the magical seasonal forests, and the volcanic and arctic extremes. Surprising wildlife stories of lynx and puffins, orca and wolves reveal the resilient spirit of Scandinavia. Myth and modernity co-exist: Odin and Thor, basejumpers and reindeer herders are all woven into this icy natural world.